Birth of a closed universe of negative spatial curvature - Da Costa, S. S. [UNESP]; Fagundes, H. V. [UNESP] (My University, 1999)
We propose a modified form of the spontaneous birth of the universe by quantum tunneling. It proceeds through topology change and inflation, to eventually become a universe with closed spatial sections of negative spatial curvature and nontrivial global topology.
Keywords: Inflation; Topology change